Evaluation of onion (Allium cepa) varieties for their suitability in tribal area of Dungarpur, Rajasthan (Current Horticulture, 2024)
An experiment was conducted to evaluate onion varieties for the suitability in Dungarpur, Rajasthan, during 2017-18 and 2018-19. Six high-yielding varieties were tested with five replications in comparison to local variety. Different treatments included onion variety Agrifound Light Red, NHRDF Red, NHRDF Red-2 NHRDF Red-3, NHRDF Red-4 and local variety Udaipur 103. The NHRDF Red-3 produced maximum height of plant (56.46 cm) and number of leaves/plant (17.30). While, NHRDF Red-4 was at par in height of plant (54.24 cm) and number of leaves/plant (17.20). The NHRDF Red recorded minimum (1.04 cm) neck thickness which was at par with Agrifound Light Red (1.11 cm), Udaipur 103 and NHRDF Red-4 (1.16 cm). However, NHRDF Red-3 recorded maximum neck thickness (1.30 cm). The maximum average fresh weight of bulb (98.48 gm) and cured weight of bulb (95.81 gm) were recorded with variety NHRDF Red-3, while NHRDF Red-4 was at par for fresh bulb (92.70 g) and for cured weight of bulbs (89.72 g). The maximum polar diameter of bulb (47.05 mm) and equatorial diameter of bulbs (48.76 mm) were recorded variety NHRDF Red-3, while NHRDF Red-4 was at par for polar diameter of bulbs (44.80 mm) and for equatorial diameter of bulbs (46.56 mm). The NHRDF Red-4 and Agrifound Light Red (153) required minimum days for maturity which was at par with local variety Udaipur 103 (162), while NHRDF Red-2 and NHRDF Red-3 (160) recorded maximum days.
Keywords: Yield; Suitability; Variety; Tribal area; Neck thickness; Polar diameter